Implementation of Marketing Strategy and SWOT Analysis In Increasing the Number of Customers At Bank BJB Syariah KCP Sumedang - Megah Dewi Anggini; Jaja Jaja (SINTESA, 2023)
The research focus contains the implementation of marketing strategiy and SWOT analysis in increasing the number of customers at Bank BJB Syariah KCP Sumedang. The purpose of the research is to find out the various kinds of superior products of collection and financing, to know the marketing strategies that are applied and to know the SWOT analysis to increase the number of customers. This research is motivated by the rapid growth of the Islamic banking world. Therefore, it is necessary to have a comprehensive marketing strategy and keep up with the digital age in order to be able to compete. In addition, the SWOT analysis can help companies determine good steps for the future of the company. The method used is descriptive qualitative with two variables, namely marketing strategy and SWOT analysis. The data collection techniques used are observation, interviews, documentation, and triangulation. Using Miles and Huberman (1984) data analysis, namely data reduction, data display and conclusion drawing. The results and discussion are various types of superior products with high customer interest, namely in the form of collection and financing (productive financing and consumptive financing). Bank BJB Syariah KCP Sumedang has a good, effective, innovative, creative marketing strategy implementation and successfully competes with other competitors. Marketing is not only done through print media but also the use of electronic media, namely social media that is always updated or commonly called digital marketing, besides that there is socialization to the community and participating in various events. SWOT analysis is considered effective to be able to find out the various strengths, weaknesses, opportunities and threats that Bank BJB Syariah KCP Sumedang must face as well as to make the right steps in the success and success of the company